Reporting and OLAP Applications for Libraries and Archives in East Java Province - Hariyanto, Yudi; Sutanto, Teguh; Romeo, Romeo (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Bapersip has eight areas that support business processes. Three areas of the recording process business using Online Transaction Process (OLTP) and Excel. Five other areas recording business processes using excel. Each month, business process data is processed by the areas to be reported. The process of making a report to transfer data from the source OLTP excel and to form reports manually. The data transfer process allows the human error such as redundant data and their data is not recorded in the report, so potentially resulting in inaccurate reports. Reports generated from the OLTP library service areas on Bapersip subfield SUNGRAM not fulfilling the needs for analysis. The solution to Bapersip problem is reporting and OLAP applications. Reporting application will help each area to create a report and eliminates the risk of human error by taking and processing the data from the source. OLAP application used to fulfill the needs of analysis using patterns based on the information you want displayed by SUNGRAM subfields.